Analysis of UNIKOM Employees’ Readiness to Adopt AI Technology to Improve Performance - Nugraha, Agung; Solihat, Manap; Wahdiniwaty, Rahma (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
The aim of this study is to examine the multidimensional readiness of Indonesia Computer University (UNIKOM) employees in accepting Artificial Intelligence (AI) technology to expedite institutional performance in achieving its status as a "World Class University". Within the framework of the cognitive revolution, UNIKOM made a major change in its evolutionary journey by inaugurating "UNIKOM X Google Learning Center" in March 2026. This study utilized a qualitative descriptive approach, combining document analysis of various strategic materials and the latest digital industry reports for the 2024-2026 period, along with in-depth interviews involving 8 employees. From the analysis of the data, it is found that psychological enablers in terms of optimism and innovativeness influence employee readiness in accepting AI technology; however, negative enablers in terms of "AI Anxiety" were also found. It is confirmed that AI technology is capable of creating 80% efficiency in operational performance in terms of academic data management. From the analysis of the data in this study, it is concluded that for digital transformation to be successful, there is a need for synergy between infrastructure and human capabilities through a continuous reskilling approach in line with the "Technology Readiness and Acceptance Model". The real impacts of this research provide a practical blueprint for higher education institutions to formulate AI-adaptive human resource policies, establish a clear Human-AI Collaboration (HAC) paradigm, and effectively mitigate technological resistance to realize a globally competitive Smart Campus environment.